Bobsleigh performance characteristics for winning design - Dabnichki, P. (Procedia Engineering, 2015)
Bobsleigh is one of the fastest and most exciting winter sport where winning margin are very slim. It is also a sport highly dependent on technology. In this work we review the technology areas likely to bring the biggest advantage to the teams and present some developments in critical areas identified. The areas reviewed are unsteady aerodynamics of the sled, ice friction and runner development, dynamic structural response and ergonomics. It is demonstrated that these three areas provide opportunity to gain performance improvement with infringing the design constraints stipulated by the regulatory body FIBT and without comprising athletes` safety.